DIGITAL MARKETING DAN BRAND DESTINATION KAMPUNG WISATA SUNGAI DINOYO SURABAYA: UPAYA PENINGKATAN DAYA SAING DIGITAL - Kristanti, Maria Mia; Budiarsi, Sri Yunan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2023)
ABSTRACT Digital marketing is increasingly becoming a key driver in communications and advertising, including tourist destinations. A well-planned digitization program can have the potential to dramatically affect a destination's brand perception and reputation. Ensuring that a brand's destination has built an online presence, as well as increasing engagement with its audience is an effective way to keep the brand in the minds of consumers. There are several tactics that can be used for digital marketing activities that can encourage the growth of tourist destinations, which will be described in this abdimas program. The implementation of community service is carried out using three methods, namely: SWOT analysis, Focus Group Discussion (FGD), and interactive discussions between related parties, academics, and campus millennials. Identification and inventory of important issues, as well as programs that have been implemented are traced through direct interviews with related parties for the previous 3 year period (2017-2020). A number of important principles are explored in this abdimas program which includes: Digital Marketing, Brand Destination, and Sustainability Management of tourist destinations. Tabulation of changes began to appear from the increase in digital iteration, and brand destination program initiatives from participants. Furthermore, it can be concluded that, deep concepts from Online Consumer Behavior to Service Quality, become an understanding that completes the elements of a successful marketing program in developing and increasing the tourist attraction of the Dinoyo river. ABSTRAK Pemasaran digital semakin menjadi pendorong utama dalam komunikasi dan periklanan, termasuk destinasi wisata. Program digitalisasi yang terencana dapat memiliki potensi untuk secara dramatis mempengaruhi persepsi dan reputasi merek destinasi. Memastikan bahwa destinasi merek telah membangun kehadiran online, serta upaya meningkatkan keterlibatan dengan audiensnya adalah cara yang efektif agar merek tetap diingat oleh konsumen. Ada beberapa taktik yang dapat digunakan untuk aktifitas pemasaran digital yang dapat mendorong pertumbuhan destinasi wisata, yang akan dipaparkan pada program abdimas ini. Pelaksanaan abdimas dilakukan dengan tiga metode, yaitu: Analisis SWOT, Focus Group Discussion (FGD), dan Diskusi Interaktif antara pihak terkait, akademisi, dan milenial kampus. Identifikasi dan inventarisasi isu penting, serta program yang telah dilaksanakan ditelusuri melalui wawancara langsung dengan pihak terkait untuk periode 3 tahun sebelumnya (2017-2020). Sejumlah prinsip penting dieksplorasikan dalam program abdimas ini yang meliputi: Digital Marketing, Brand Destination, dan Manajemen Kerberlanjutan destinasi wisata. Tabulasi perubahan mulai nampak dari peningkatan iterasi digital,dan inisiastif program destinasi merek dari peserta. Selanjutnya, dapat disimpulkan bahwa, konsep mendalam mengenai Online Consumer Behavior hingga Service Quality, menjadi pemahaman yang melengkapi elemen sukses program pemasaran dalam pengembangan dan peningkatan daya tarik wisata sungai Dinoyo.